Revisiting the Map of the Territory - Kjell Rubenson (Adult Education Research Conference, 2000)
The purpose of this study was to revisit the article The Map of the Territory, written twenty years ago. The analysis is based on a review of major journals, conference proceedings and some key books. The review reveals how the landscape is being shifted by paradigmatic changes in the social sciences and the broadening of the boundary of adult education practice. The separation of empirically and normatively informed arguments is seen as a major problem for the drawing of the map